Investigating Effect of Students' and Coaches' emotional intelligence on academic achievement with mediation of sport success - Rizvandi, Aye (2020)
This research aims to study the effect of students’ and coaches’ emotional intelligence (EI) on academic achievement (AA) with mediation of sport success (SS). This is a causative research and it is applied research in terms of the purpose. The population consists of second grade students and their coaches. For sampling, 33 sport teams were identified that had 347 second grade students, and the research questionnaires were distributed among them. The results showed that EI of students and coaches have significant effect on SS. In addition, students’ EI have a significant effect on AA. Also, the EI of students and coaches have indirect effect on AA through SS. Finally, considering the importance of EI, coaches and students should perceive the EI functions and aspects to utilize it in different situation.